An investigation of sodium silicate added malaccan red clay for slip casting process - Ahmad, Mohamad Asmadi (2014)
The development of local pottery industries in any area is dependent on the availability of a high quality local clay resource. This study explores the possibility of using Malaccaoriginated clay to replace Sayong clay in producing ceramic pottery using slip casting technique. Red clay from Kampung Sungai Petai, Malacca (Malaccan red clay) is selected as a raw material due to close vicinity of the resource to KKTM Malacca. The Malaccan red clay was characterized in term of mineralogy and chemical composition by using X-Ray Diffraction machine and Energy Dispersive X-Ray Fluorescence machine. The optimization of the dispersant dosage (Sodium silicate, Na2Si03) varying from 0.20% wt. to 0.40% wt of total raw material powder was determined by the agglomeration measurement size and sedimentation test. Then the study is continued with the determining optimum solid loading. Slurry with solids loadings of 60%, 65%, 70%, 75% and 80% by weight was determined by viscosity and the casting rate measurement. After that, test bar was cast by using slurry with the optimum dispersant dosage and the optimum solid loading. The test bar was fired at temperatures of 1100, 1150, 1200, 1250, 1300 and l 350°C and then underwent physical analyses according to the specific ASTM standard. Optimum sintering temperature on test samples was determined by water absorption and firing shrinkage measurement. Optimum dispersant dosage was 0.30 wt %. Optimum solid loading was determined at 75% wt indicated by viscosity reading below and near to l Pa.s and the highest casting rate value with good cosmetic appearance. Optimum sintering temperature is at 1250°C identified by its maximum linear shrinkage. Malaccan red clay contains high percentage of hematite (Fe20 3), and red colour comes from iron inside the mineral so it should categorize in red clay classification. Apart from hematite phase, characteristic peaks of quartz, mullite, kaolinite and montmorillonite were identified. Occurrences of kaolinite and montmorillonite act as a body of the ceramic products, however quartz and mullite as a filler and little fluxing agent exist such as elements of K10 and Na20 . By all ingredients, so definitely this clay can be made as an independent raw material for producing ceramic products without added others filler and fluxing agents. Malaccan red clay also has ability to disperse well after added with sodium silicate and has low enough viscosity with high solids loading which are very important criteria in slip casting process. It also has a reasonable matured temperature and suitable for the manufacture of terra cotta products. With all of the investigation, sodium silicate added Malaccan red clay is suitable for slip casting process.